Evaluasi Sistem Jaringan Distribusi Air Bersih PAMSIMAS Desa Lubuk Tilan Kabupaten Siak Menggunakan EPANET 2.2 - Fakar, Lintang Putri; Joleha, Joleha; Suprayogi, Imam (Jurnal Teknik Sipil Terapan (JTST), 2025)
The distribution of clean water remains a challenge, especially in rural areas. To address this issue, the government has implemented the PAMSIMAS Program as an alternative solution for providing clean water. Howev er, due to the conventional distribution system being less than optimal, further analysis is conducted through numer ical simulations using the EPANET 2.2 software to identify problems and formulate improvement solutions. Existing condition data and technical specifications of the pipe network are used as input for the analysis, referring to the Minister of Public Works Regulation No. 18 of 2007 to evaluate pressure, velocity, and head loss at each node and pipe. Three simulations were conducted: the existing condition, system improvement simulation, and projection of clean water needs until 2040, using the geometric method to calculate population growth. In 2024, the water de mand for 224 residents was recorded at 0.257 liters/second, indicating that the flow velocity did not meet the re quired standard. As a result, improvements such as pump replacement and pipe diameter adjustments were neces sary. The 2040 projection estimates a population increase to 1,470 people with a constant service level of 18.93%, leading to a projected water demand of 0.319 liters/second. The simulation results indicate that replacing the 2 HP pump with a 3 HP unit, along with adjusting the pipe diameter from 40–50 mm to 20–40 mm.